Feasibility of a Short-Term Virtual Reality Balance Intervention to Improve Mobility Smoothness in Parkinson's Disease - Schuch, Clarissa Pedrini; Balbinot, Gustavo; Bonilla, Marilley Nohely; Guedes Machado, Andréa; Oliveira, Alcyr Alves de (Frontiers in Virtual Reality, 2020)
Parkinson’s disease (PD) is a neurodegenerative condition often associated with reduced balance and gait control. Virtual reality (VR) is a promising intervention for enhancing rehabilitation efficiency and may assist in overcoming functional limitations. The objective of this study was to evaluate the feasibility, safety and efficacy of a 5-weeks VR intervention in increasing mobility smoothness in participants with PD. Participants were assessed using functional mobility tasks - Timed Up and Go (TUG) and 10-meter walking test (10MWT) and cognitive function tests. A total of 23 participants with a diagnosis of PD were randomly assigned to groups of VR or control interventions. In the VR group, for each session, participants received a VR–based balance training, for 20 minutes, preceded by 8 minutes of total body warm-up (total of 10 sessions over five weeks). Participants in the control group received 20 minutes of psychoeducation without a structured exercise program (twice a week). All screened participants engaged and completed a total of 10 VR-based intervention sessions. VR-based balance training caused no significant improvement in mobility smoothness for TUG or 10MWT (p > 0.05). Similarly, cognitive function was not affected by the VR intervention (p > 0.05). The outcomes of this study suggest that ten-twenty minutes of VR-based intervention is a feasible and safe rehabilitation activity. However, it was insufficient to promote improvement in mobility smoothness and cognitive function in participants with PD. A combination of task-specific training in the virtual and physical environments is warranted for future study designs.